The UPLB Speech Communication Identity: Weaving Humanities Roots, Institutional Practices, and Disciplinary Trajectories - Sayuno, Cheeno Marlo M.; Cruz, Carson Jeffrey O.; Taduran-Buera, Jea Agnes; Blanco, Katrina Anne E. (Philippine Humanities Review, 2025)
The Department of Humanities (DHUM) of the University of the Philippines Los Baños (UPLB) has been offering the BA Communication (BACA) program since 1974. The program is the University’s first liberal arts program anchored on the premise that communication is interactive, democratic, and liberalizing. It aims to produce graduates who demonstrate proficiency in various theories of language, communication, literature, and performance; and exhibit analytical and integrative skills in the application of these theories in the cultural and creative industries and other settings. The program has three major areas: speech communication, writing, and theater arts. In this paper, we interrogate speech communication as a field of study by looking at the development of communication studies as an academic discipline, on the one hand, and as a major area in the BACA program situated within the broad disciplines of the humanities, on the other. Specifically, we aim to reconceptualize speech communication both as a major area in the BACA program and as an academic study by looking at the history of the BACA program, the teaching and research practices of the DHUM faculty, and the research engagements of our BACA students. We propose a three-strand framework of speech communication based on this reconceptualization, one that reimagines the identity of the speech communication major area of the BACA program and the Communication Division of DHUM. At the same time, we aim to enhance the liberal and generalist orientation of the BACA program and open possibilities for an independent speech communication program at UPLB in the future.